Customary Land Conversion in African Cities - Pierre M. Picard; Harris Selod (Institute of Labor Economics (IZA), 2023)
We propose an urban land use model to discuss the conversion of customary agricultural land to formal and informal residential land in a developing country city. Because customary land sales are insecure, migrant buyers face a risk of eviction, which affects land markets in non-trivial ways. Both tenure risk and asymmetric information cause the city extent and population to be too small. Empirical tests of the model for Bamako, Mali, confirm the existence of tenure insecurity and information asymmetry in the primary but not in the secondary land market, consistently with information revelation after initial sales by customary holders.
Keywords: O12; R14; P14; 330; urbanization; land markets; property rights; land tenure formalization; market failure